Humanistic Solutions to Prevent Bullying in Schools: Collaboration and Positive Environments: Solusi Humanistik Mencegah Bullying di Sekolah: Kolaborasi dan Lingkungan Positif - Mustofah, Ainun; Nurdyansyah, Nurdyansyah (Indonesian Journal of Education Methods Development, 2025)
General Background : In the dynamic landscape of modern times, education extends beyond knowledge transfer to creating an optimal environment for child development. Specific Background : A significant challenge in this regard is school bullying, which poses a serious threat to children's mental and emotional well-being. Knowledge Gap : While child-friendly schools are a known solution, there is a need for a new product: a future school completely free of bullying. Aims : This study, using a humanistic approach, aims to develop a new framework for a bullying-free school where students can learn comfortably and joyfully. Results : The research found that creating a child-friendly school requires a multifaceted approach. Key actions include: collaboration between parents and schools, anti-bullying training for teachers, fostering a friendly school atmosphere, designing a beautiful and green environment, and using eco-friendly and child-friendly materials for infrastructure and facilities. Novelty : The novelty lies in proposing a comprehensive model for a bullying-free school as a "second home" for students. Implications : These findings provide a practical roadmap for schools to become safer, more supportive spaces, thereby protecting children's welfare and improving their learning experience. Highlights :  Creating a child-friendly school environment requires a humanistic approach that views children as individuals. Key actions to prevent bullying include collaboration between parents and schools, anti-bullying training for teachers, and creating a friendly school atmosphere. Bullying is a serious threat to a child's mental and emotional well-being, and a child-friendly school is a crucial step to protect them. Keywords : Child-Friendly Schools, Bullying Prevention, Humanistic Approach, Teacher Training, Parents Collaboration.